A ferry merry Christmas : a novel [large type] - Macomber, Debbie (Random House Large Print, 2025)
A delayed ferryboat brings people together in the best of ways during the holiday season in this enchanting Christmas novel from #1 New York Times bestselling author Debbie Macomber. Avery and Reed Bond grew up sharing a close-knit relationship, weathering life's storms side by side. Even so, Avery often finds herself exasperated by her brother's relentless matchmaking, while Reed can't resist teasing his sister-after all, isn't that what siblings do?Facing their first Christmas without their beloved Grams, the woman who lovingly raised them, Reed and Avery decide to spend the holiday together at Reed's home. However, their plans take an unexpected turn when the ferry Avery's traveling on stalls in the middle of Puget Sound, stranding its passengers and leaving Reed waiting a now undetermined length of time for her arrival. What is at first an inconvenience threatens to ruin the plans of a number of commuters, but Avery and Reed soon discover that this unforeseen delay might end up being be a perfectly timed blessing in disguise.While stuck on the ferry, Avery meets a handsome sailor and witnesses a Christmas miracle that reignites her belief in the holiday spirit. Meanwhile, Reed runs into a coworker who's also waiting for a family member to arrive, and sparks a surprising and delightful connection.In this tale of holiday magic, the Bond siblings find themselves taking a chance on love, proving that sometimes the best moments in life come when we least expect them.